Core-shell Fe3O4-ZnO nanoparticles decorated on reduced graphene oxide for enhanced photoelectrochemical water splitting. Issue 3 (April 2015) - Yusoff, N.; Kumar, S. Vijay; Pandikumar, A.; Huang, N.M.; Marlinda, A.R.; An'amt, M.N.
Abstract: Herein, we report the hydrothermal synthesis of hetero-nanostructures of core-shell Fe3 O4 -ZnO nanoparticles with rGO sheets having different weight ratios and characterized by suitable techniques, including high-resolution transition electron microscopy (HRTEM), field emission scanning electron microscopy (FESEM), energy dispersive x-ray analysis (EDX), x-ray diffraction (XRD), Raman microscopy, photoluminescence spectroscopy (PL) and UV–vis spectroscopy. The as-prepared rGO/Fe3 O4 -ZnO nanocomposite materials were used for photoelectrochemical water splitting. The photoelectrochemical results showed that the photocurrent density increased from 520 μA/cm 2 to 850 μA/cm 2 at 1.23 V RHE with an increase in the (Zn(OH)2 precursor loading. The addition of graphene effectively enhanced the photoelectrochemical performance of the core-shell Fe3 O4 -ZnO hybrid material. We further demonstrated that the Zn(OH)2 content in the composite played an important role in the determination of the electronic interaction strength with rGO sheets, and the formation of the core-shell Fe3 O4 -ZnO complex helped to slow the recombination rate of electron-hole pairs, which also affected the photoelectrochemical performance. This rGO/Fe3 O4 -ZnO nanocomposite material could be a promising candidate for solar hydrogen production.